The res gestae: a reformulation / Rosli Mohd Sidek - Mohd Sidek, Rosli (Faculty of Law, 1985)
"Hearsay" in its legal sense is confined to that kind of evidence, which does not derive its credibility solely from the credit due to the witness himself, but rest also in part on the veracity and competency of some other person from whom the witness may have received the information. The general rule is that hearsay is excluded and best evidence must always be given. Its excluded on the ground that it is always desirable in the interest of justice to get the person whose statement is relied upon, into court for its examination in the regular way in order sources of inaccuracy can be best brought to light and exposed by the test of cross examination.